Karakteristik dan Prinsip Bahan Ajar - Srihartini, Yusi; Mulyana, Agus; Purwaningsih, Yuli (Ikatan Dai Indonesia, 2025)
Islamic Religious Education (PAI) plays a very important role in shaping the character and noble morals of students. The quality of PAI teaching materials is one of the key factors in the success of the learning process. And aims to describe the principles and characteristics of effective PAI teaching materials. PAI teaching materials are learning tools designed to help teachers and students achieve the goals of PAI education. Good and quality teaching materials will make it easier for students to understand Islamic teachings, so that they can deepen and practice them in their daily lives. Principles such as relevance, consistency, and sufficiency are important foundations in compiling PAI teaching materials. In addition, the unique characteristics that distinguish PAI teaching materials from other teaching materials provide added value in realizing the ideals of Islamic Religious Education and Character for students. By paying attention to these principles and characteristics, Islamic Religious Education teaching materials are expected to help students achieve the desired learning goals, namely to become Muslim individuals who are faithful, pious, and have noble morals.